1992
DOI: 10.1037/0021-9010.77.6.952
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of behavior modeling and the cultural assimilator in cross-cultural management training.

Abstract: This field experiment examined the individual and combined effects of behavior modeling and the cultural assimilator in the cross-cultural management training of 65 U.S. Government employees. Training evaluation criteria of learning, behavior, and reactions were used, and the results were generally supportive of the greater effectiveness of a combined approach. Participants receiving the combination of methods displayed significantly higher performance on a role play task (behavior evaluation) than a no-traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 46 publications
0
49
0
1
Order By: Relevance
“…For example, there was a corrected correlation between cross-cultural training and expatriate job performance of .39. Since this meta-analysis was published, other primary empirical studies have further confirmed the effectiveness of cross-cultural training programs (Bhawuk, 1998;Hammer & Martin, 1992;Harrison, 1992).…”
Section: Importance Of Cross-cultural Trainingmentioning
confidence: 99%
“…For example, there was a corrected correlation between cross-cultural training and expatriate job performance of .39. Since this meta-analysis was published, other primary empirical studies have further confirmed the effectiveness of cross-cultural training programs (Bhawuk, 1998;Hammer & Martin, 1992;Harrison, 1992).…”
Section: Importance Of Cross-cultural Trainingmentioning
confidence: 99%
“…In fact, whereas consulting is largely informational, coaching is heavily inspirational and focused on skill development. Furthermore, a mentor is a guide and advisor that focus on enhancing a person's role effectiveness (Waters, Clarke, Ingall, & Dean-Jones, 2003) and on promoting a person's professional and/or personal development and not a specific task (Fisher, 1994), whereas a trainer aims at teaching specific skills or knowledge to the client (Harrison, 1992). Moreover, managerial work is more often associated with decision making, work overload, role related problems and uncertainty (French, Caplan, & van Harrison, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Either didactic or experiential cross-cultural learning programs are better than no training at all, and are better than in-country training without guided learning (Goldstein & Smith, 1999;Korhonen, 2002;Sizoo, Serrie, & Shapero, 2007;Soeters & Recht, 2001), but neither is necessarily better than the other (Hammer & Martin, 1992;Harrison, 1992). Augmenting experiential CCTE with didactic CCTE aids learning (Harrison, 1992;McDaniel, McDaniel, & McDaniel, 1988).…”
Section: Cross-cultural Training and Educationmentioning
confidence: 99%
“…Augmenting experiential CCTE with didactic CCTE aids learning (Harrison, 1992;McDaniel, McDaniel, & McDaniel, 1988).…”
Section: Cross-cultural Training and Educationmentioning
confidence: 99%